Three-dimensional genome organization in normal and malignant haematopoiesis. Issue 4 (July 2018) - Cuartero, Sergi; Merkenschlager, Matthias
Abstract : Purpose of review: The three-dimensional organization of the genome inside the nucleus impacts on key aspects of genome function, including transcription, DNA replication and repair. The chromosome maintenance complex cohesin and the DNA binding protein CTCF cooperate to drive the formation of self-interacting topological domains. This facilitates transcriptional regulation via enhancer–promoter interactions, controls the distribution and release of torsional strain, and affects the frequency with which particular translocations arise, based on the spatial proximity of translocation partners. Here we discuss recent insights into the mechanisms of three-dimensional genome organization, their relationship to haematopoietic differentiation and malignant transformation. Recent findings: Cohesin mutations are frequently found in myeloid malignancies. Significantly, cohesin mutations can drive increased self-renewal of haematopoietic stem and progenitor cells, which may facilitate the accumulation of genetic lesions and leukaemic transformation. It is therefore important to elucidate the mechanisms that link cohesin to pathways that regulate the balance between self-renewal and differentiation. Chromosomal translocations are key to lymphoid malignancies, and recent findings link three-dimensional genome organization to the frequency and the genomic position of DNA double strand breaks. Summary: Three-dimensional genome organization can help explain genome function in normal and malignant haematopoiesis.